2021
DOI: 10.3389/fped.2021.740951
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte and Platelet-to-Lymphocyte Ratio in Univentricular Patients From Birth to Follow-Up After Fontan—Predicting Lymphatic Abnormalities

Abstract: Background: Reliable laboratory parameters identifying complications after Fontan surgery including the lymphatic abnormalities and the development of protein-losing enteropathy (PLE) are rare. Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocte ratio (PLR) are inflammatory markers and have been studied to predict outcome and prognosis in various diseases. The aim of this study was to investigate NLR and PLR from birth to follow-up after Fontan and evaluate their use as prognostic parameters for sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Moosmann et al recommended calculating NLR and PLR for univentricular patients during the course of total cavopulmonary connection and follow-up. 56 In their study, NLR and PLR correlated with the degree of lymphatic malformations, which are associated with early complications after Fontan surgery and Fontan failure, and may also occur after Glenn surgery despite a lack of clinical manifestation. The authors suggested that patients with higher values require closer monitoring and evaluation for signs of Fontan complications, such as lymphatic malformations and protein-losing enteropathy (PLE).…”
Section: Cardiopulmonary Bypassmentioning
confidence: 88%
See 1 more Smart Citation
“…Moosmann et al recommended calculating NLR and PLR for univentricular patients during the course of total cavopulmonary connection and follow-up. 56 In their study, NLR and PLR correlated with the degree of lymphatic malformations, which are associated with early complications after Fontan surgery and Fontan failure, and may also occur after Glenn surgery despite a lack of clinical manifestation. The authors suggested that patients with higher values require closer monitoring and evaluation for signs of Fontan complications, such as lymphatic malformations and protein-losing enteropathy (PLE).…”
Section: Cardiopulmonary Bypassmentioning
confidence: 88%
“…Arterial hypertension is an increasing problem in children due to obesity, sedentary lifestyle and excessive [21], [27], [29], [30], [31], [32], [33], [41], [44], [45], [46], [55], [56], [57], [59], [60], [62], [63], [71] Platelet count Kawasaki disease -coronary artery aneurysms acute rheumatic carditis arterial hypertension [20], [30], [41] PLR Fontan patients neonatal sepsis ECMO use IVIG resistance in Kawasaki disease arterial hypertension [21], [41] MLR necrotizing enterocolitis in PDA children severity of valvular involvement in acute rheumatic carditis [33], [35] ECMO -extracorporeal membrane oxygenation; ICU -intensive care unit; IVIG -intravenous immunoglobulin; MLR -monocyte-to-lymphocyte ratio; NLR -neutrophil-to-lymphocyte ratio; PDA -patent ductus arteriosus; PLE -protein-losing enteropathy; PLR -platelet-to-lymphocyte ratio.…”
Section: Arterial Hypertensionmentioning
confidence: 99%
“…In the pediatric population, the neutrophil-lymphocyte-ratio has been demonstrated to be associated with, and have prognostic implications in the setting of, several clinical occurrences such as pleural effusion after cardiac surgery, duration of mechanical ventilation after cardiac surgery, length of stay after cardiac surgery, low cardiac output after cardiac surgery, cardiac dysfunction, refractory Kawasaki disease, coronary artery lesions with Kawasaki disease, lymphatic anomalies after the Fontan procedure, carditis with Rheumatic fever, reactive airway disease, and necrotizing enterocolitis among others [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%